2011
DOI: 10.1080/10926771.2011.562478
|View full text |Cite
|
Sign up to set email alerts
|

How Do Social Interactions with a Significant Other Affect PTSD Symptoms? An Empirical Investigation with a Clinical Sample

Abstract: Social support and coping are both related to posttraumatic stress disorder (PTSD) symptoms, but the mechanisms underlying their relationships remain unclear. This study explores these relationships by examining the perceived frequency of supportive and countersupportive interactions with a significant other in PTSD patients. Ninety-six participants with PTSD were recruited and completed questionnaires assessing social interactions, ways of coping, and PTSD symptoms. Associations of social interactions (r = 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…Guay, Beaulieu-Prevost, Beaudoin and St-Jean-Trudel (2011) found a direct association between social support and PTSD. In a meta-analysis of risk factors for PTSD, Brewin, Andrews and Valentine (2000) found lack of social support to be one of the most significant predictors for PTSD.…”
mentioning
confidence: 93%
“…Guay, Beaulieu-Prevost, Beaudoin and St-Jean-Trudel (2011) found a direct association between social support and PTSD. In a meta-analysis of risk factors for PTSD, Brewin, Andrews and Valentine (2000) found lack of social support to be one of the most significant predictors for PTSD.…”
mentioning
confidence: 93%
“…It is characterized by victims (or witnesses) of trauma experiencing intrusive thoughts (e.g., nightmares or difficulties concentrating), avoidance behaviours (e.g., avoiding activities that might remind them of the trauma), negative alterations in cognition and mood (e.g., persistent and distorted blame of self or others, and persistent negative emotional state), and alterations in arousal and reactivity (e.g., reckless or self‐destructive behaviours, hypervigilance, and exaggerated startle responses; American Psychiatric Association, ). Empirical evidence showed that social support could have buffering effects on PTSD (Adams & Boscarino ; Andrews, Brewin, & Rose, ; Avery & McDevitt‐Murphy, ; Guay, Billette, & Marchand, ; Guay et al, ; Laffaye, Cavella, Drescher, & Rosen, ; Pietrzak et al, ; Schnurr, Lunney, & Sengupta, ). Specifically, lack of social support after the traumatic event is one of the strongest social factors that predicts PTSD.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical specifications have recently been added to this model. Perceived support from others and coping strategies have been shown to affect PTSD symptoms independently (Guay et al, 2011). Thus, coping strategies and social support could very well be related variables that have an independent impact on PTSD, which in turn has an impact on quality of life.…”
Section: Ptsd Social Support and Coping Strategies As Predictors Ofmentioning
confidence: 99%
“…The Questionnaire on Social Support Behaviors in Anxious Situations (QSBA) -The QSBA (Guay et al, 2011;Guay, Marchand, & O'Connor, 2003) is a 31-item selfreport questionnaire assessing the perceived frequency of supportive social interactions (QSBA-positive: 9 items) and counter-supportive social interactions (QSBA-negative: 22 items) with a significant other in anxiety-provoking situations. The QSBA was developed and validated with university students and with PTSD outpatients (Beaudoin, St-Jean Trudel, Nachar, Guay, & Marchand, 2008;St-Jean-Trudel, Guay, Marchand, & O'Connor, 2005).…”
Section: The Ways Of Coping Questionnaire-short Version (Wcq-s)-the Omentioning
confidence: 99%